2005
DOI: 10.1021/jp052445l
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Enhancement of Oxygen Evolution in Thylakoid Membranes:  Modeling the Effect of Light Intensity and β-Cyclodextrin Concentration

Abstract: Electron transport through photosystem II, measured as oxygen evolution (OE), was investigated in isolated thylakoid membranes treated with beta-cyclodextrin (beta-CD, a cyclic oligosaccharide constituted of seven alpha-d-glucose residues linked by alpha-1,4 glycosidic bonds) and irradiated with white light of variable intensity. First, we found that the light-response curves of oxygen evolution are well fitted with a hyperbolic function, the shape of which is not affected by the beta-CD concentration. Second,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…[18][19][20] but the theoretical discussion of those observations was not attempted. In two former papers, 13,14 we showed that the variation of oxygen evolution with the light intensity in PSII in steady state conditions can be formulated according to the Langmuir adsorption isotherm for heterogeneous catalysis where the photons interaction with the chlorophylls in the PSII reaction center is assumed to be a heterogeneous reaction in which the light is represented as a stream of particles instead of an electromagnetic wave. However, we show here that eqn (1) is but a special case of a more general mathematical expression for a number n of interaction (or binding) sites of the photons in the PSII reaction center, that is, a cooperative interaction of incident photons with the chlorophylls, and most likely also the pheophytins, in the PSII reaction center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] but the theoretical discussion of those observations was not attempted. In two former papers, 13,14 we showed that the variation of oxygen evolution with the light intensity in PSII in steady state conditions can be formulated according to the Langmuir adsorption isotherm for heterogeneous catalysis where the photons interaction with the chlorophylls in the PSII reaction center is assumed to be a heterogeneous reaction in which the light is represented as a stream of particles instead of an electromagnetic wave. However, we show here that eqn (1) is but a special case of a more general mathematical expression for a number n of interaction (or binding) sites of the photons in the PSII reaction center, that is, a cooperative interaction of incident photons with the chlorophylls, and most likely also the pheophytins, in the PSII reaction center.…”
Section: Discussionmentioning
confidence: 99%
“…In two former papers, 13,14 it was shown that in steady state conditions of coupled reactions where slow and fast kinetics alternate 15 the dependence of oxygen evolution in PSII particles on the incident light intensity is well described by the Langmuir adsorption isotherm for heterogeneous catalysis. 16 In this approximation, the Chl molecules in the PSII reaction center are the adsorption surfaces (or heterogeneous catalysts) and the incident photons the substrate, or the reagent, in accordance with Turro's concept 17 of light being represented in photochemical reactions as a stream of particles instead of an electromagnetic wave.…”
Section: Introductionmentioning
confidence: 99%
“…The equations in Table 1 are dynamically linear because changes in a particular property of a PSII population, such as the PSII functional crosssection, have a direct and proportional effect on photosynthetic rates and yields. Recent studies, however, suggest that the photosynthetic light reactions are not so clearly linear in this manner but rather can exhibit strong nonlinear dynamics (Nedbal and Březina 2002, Nedbal et al 2003, Fragata and Dudekula 2005, Rascher and Nedbal 2006. If the capture and uptake of photons at the photosystem level is sufficiently nonlinear in a dynamical sense, then small changes in a particular PSII property Dashed lines indicate simulations where the effect of PSII connectivity was ignored and p was fixed to 0.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, suggest that the photosynthetic light reactions are not so clearly linear in this manner but rather can exhibit strong nonlinear dynamics (Nedbal and Březina 2002, Nedbal et al. 2003, Fragata and Dudekula 2005, Rascher and Nedbal 2006). If the capture and uptake of photons at the photosystem level is sufficiently nonlinear in a dynamical sense, then small changes in a particular PSII property may actually have a disproportionately strong effect on light‐harvesting rates or yields, which would not occur in a dynamically linear system.…”
mentioning
confidence: 99%
See 1 more Smart Citation